Job satisfaction among employees in Tebrau Teguh Berhad / Nurhayati Esah - Esah, Nurhayati (Faculty of Business and Management, 2010)
Job satisfaction is an important aspect in creating efficiency and effectively working environment within the organization. Thus, this study evaluates the job satisfaction of employees in the company and aims to identify the factors that contribute to job satisfaction and the relationship between them. The researcher argues that one tool is not sufficient to identify certain factors related to job satisfaction as well as lack of research conducted on the job satisfaction among employees in the property developer company. Therefore, the study combines some of the major factors to measure the participants’ job satisfaction in the property developer company which are compensation package, relationship with supervisor, promotion opportunity and relationship with co-workers. This study’s results, which are based on data gathered from the questionnaire which been distributed to 65 employees within the company, Tebrau Teguh Berhad identified that all of these 4 factors which are compensation package, relationship with supervisor, promotion opportunity and relationship with co-worker has a significant relationship with the job satisfaction This finding found due to the correlation analysis implemented was resulted less than 0.05. As a conclusion, recommendation has been given throughout this study to the company and also, for the future studied in way for a better improvement.